Minimal twist for the Standard Model in noncommutative geometry: The field content - Filaci, Manuele; Martinetti, Pierre; Pesco, Simone (Physical review. D, 2021)
Noncommutative geometry provides both a unified description of the Standard Model of particle physics together with Einstein-Hilbert action (in Euclidean signature) and some tools to go beyond the Standard Model. In this paper, we extend to the full noncommutative geometry of the Standard Model the twist (in the sense of Connes-Moscovici) initially worked out for the electroweak sector and the free Dirac operator only. Namely, we apply the twist also to the strong interaction sector and the finite part of the Dirac operator. To do so, we are forced to take into account a violation of the twisted first-order condition. As a result, we still obtain the extra scalar field required to stabilize the electroweak vacuum and fit the Higgs mass, but it now has two chiral components. We also get the additive field of 1-forms already pointed out in the electroweak model, but with a richer structure. Finally, we obtain a pair of Higgs doublets, which are expected to combine into a single Higgs doublet in the action formula, as will be investigated in the second part of this work.